Growth patterns in mesophotic octocorals: Timing the branching process in the highly-valuable Mediterranean Corallium rubrum. (20th March 2016) - Benedetti, Maria Carla; Priori, Cristina; Erra, Fabrizio; Santangelo, Giovanni
Abstract: This study examined colony growth in the long-lived red coral Corallium rubrum, a slow growing octocoral endemic to the Mediterranean Sea and neighboring Atlantic areas and one of the most valuable of all marine species. Age and growth rate were determined on 165 sections of colony bases and branches by means of a validated age dating method in populations living between 50 and 130 m in the NW Mediterranean. The ratio between minimum and maximum diameter remained constant, indicating proportional growth of colony bases. No significant difference was found between the growth rate of bases and branches. A significantly different branching pattern (colony height/number of branches) and average growth rate were found between the colonies of the different geographic areas. As growth rate decreases with age, this was due to the different age structure of the two samples. The maximum lifespan was found to be 106 years, a value not determined previously for C. rubrum colonies, and the average age of colonies at first branching was about 10 years. Linear growth varied widely between colonies as well as between branches in the same colony, confirming the lack of any strict relation between height and age. The study illustrates the growth of a mesophotic, heavily exploited Corallidae. Graphical abstract: